Astaxanthin Function as Colour Source in Ornamental Fish - dani, citra; Diniariwisan, Damai (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
Ornamental fish are one of the fishery commodities that continue to grow in Indonesia, with production increasing every year. Color is the most important factor that determine ornamental fish value in market. There are several factors that affect color of ornamental fish, genetics, fish health and the feed given. Astaxanthin, a type of carotenoid, plays an important role in the coloring of ornamental fish. It is known that astaxanthin can produce red colour on fish skin. Astaxanthin cannot be synthesized from within the fish’s body, so it requires external sources through feed. This article was written using a journal review method from several journal and was explained descriptively. The results of the article review obtained were that there are two sources of astaxanthin that are widely used today, namely chemical synthesis and extraction from natural materials. Synthetic astaxanthin has a more economical price but its bioactivity is lower than natural astaxanthin. Natural sources of astaxanthin can be obtained from the microalgae Haematococcus pluvialis, crabs and shrimp. H. pluvialis is a natural source of astaxanthin with the highest content, which can be produced through cultures that are given stress such as changes in temperature and lighting. In addition, shrimp and crabs also accumulate astaxanthin in the body through the consumption of feed rich in carotenoids. Several studies have shown that giving astaxanthin in feed can significantly increase the brightness of the color in ornamental fish.